Visual response effects of western flower thrips manipulated by different light spectra - Liu, Qihang; Jiang, Yueli; Miao, Jin; Gong, Zhongjun; Li, Tong; Duan, Yun; Wu, Yuqing (International Journal of Agricultural and Biological Engineering, 2019)
To understand how spectral light wavelength affects thrips visual sensitivity, the selective response and the approach sensitivity of western flower thrips were examined. The results showed that light intensity affected thrips selective sensitivity to different spectra, with good visual sensitivity to blue, ultraviolet (UV), and green light changes to UV, violet, and yellow light when illumination increased from 120 lx to 6000 lx. Red light was the sensitive spectral light driving thrips to respond to sensitive light. Under illumination, the best sensitivity response to spectra was violet, while under light energy, this changed to UV when light energy was increased to 120 mW/cm2. However, the photo-stimulus properties (illumination or light energy) did not affect the optimal approach sensitivity to UV light. Furthermore, when illumination or light energy stimulated thrips to select two different spectral lights, the total response sensitivity to 12000 lx of UV and violet light were the best (83.27%), while at 60 mW/cm2 of UV and yellow light was the best (82.15%). But different photo-stimulus properties influenced on the total approach sensitivity to the stimulation of two different spectral lights when the intensity of light increased, showing that to 12000 lx of violet and green light was the best (53.18%), while for 120 mW/cm2 of UV and green light was the best (47.74%). The thrips visual selection response effects stimulated by illumination were different from that induced by light energy, and originated from the thrips different bio-regulatory effects caused by the intensity of light energy of illumination and the intensity of illumination of light energy. Therefore, different photo-stimulus effects can manipulate thrips visual sensitivity to enhance the phototactic effect.Keywords: western flower thrips, visual response effect, spectral light, illumination, light energyDOI: 10.25165/j.ijabe.20191205.4922Citation: Liu Q H, Jiang Y L, Miao J, Gong Z J, Li T, Duan Y, et al. Visual response effects of western flower thrips manipulated by different light spectra. Int J Agric & Biol Eng, 2019; 12(5): 21–27.